CORPUS LINGUISTICS STUDY: ANALYZE THE USE OF PREPOSITIONS IN “FIVE FEET APART” NOVEL BY RACHEL LIPPINCOTT - Rosa Sangga Pratiwi (Faculty of Education and Teachers Training, 2021)
Indonesia is one of the countries which used English as a Foreign Language (EFL). English is studied in schools and universities but not widely used as an official language. As the world is becoming a globalization era, it is the international language that people should learn. They have to master reading, speaking, listening, and writing skills. There are many different uses of grammar in a novel that can use to improve English skills. In writing skills, deep grammar knowledge is required, including prepositions. In the Five Feet Apart novel, the author uses various prepositions, such as at, in, and on. There are rules in each of those skills, such as the use of correct prepositions in writing. Prepositions are essential to make good sentences. This study aims to examine the proper use of prepositions through different uses of prepositions in a novel. It uses a qualitative method by collecting prepositions from the Five Feet Apart novel by Rachel Lippincott. The analysis reveals which prepositions frequently appear in the story.